Socialism in Provence, 1871-1914 : a study in the origins of the modern French Left - Judt, Tony (New York University Press, 2011)
Departing from the usual emphasis on an urban and industrial context for the rise of socialism, Socialism in Provence 1871-1914 offers instead a reinterpretation of the early years of Marxist socialism in France among the peasantry. By focusing on a limited period and a particular region, Judt provides an account both of the character of political behavior in the countryside and of the history of left-wing politics in France.